2019
DOI: 10.1007/s00383-019-04469-2
|View full text |Cite
|
Sign up to set email alerts
|

Trends in pediatric-adjusted shock index predict morbidity in children with moderate blunt injuries

Abstract: PURPOSE: Trending the pediatric-adjusted shock index (SIPA) after admission has been described for children suffering severe blunt injuries (i.e. injury severity score (ISS)>15). We propose that following SIPA in children with moderate blunt injuries, as defined by ISS 10-14, has similar utility. METHODS: The trauma registry at a single institution was queried over a seven year period. Patients were included if they were between 4-16 years old at the time of admission, sustained a blunt injury with an ISS 10-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The SIPA was reported to have a correlation with ISS, ventilator use, length of hospital stay, early need for blood product transfusion, and mortality in pediatric trauma patients [15,28,29]. In our study population, the SIPA was not correlated with the ISS, need for MT, or outcomes, but among the patients with non-severe TBI, those who did not survive had higher initial SIPA values.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The SIPA was reported to have a correlation with ISS, ventilator use, length of hospital stay, early need for blood product transfusion, and mortality in pediatric trauma patients [15,28,29]. In our study population, the SIPA was not correlated with the ISS, need for MT, or outcomes, but among the patients with non-severe TBI, those who did not survive had higher initial SIPA values.…”
Section: Discussionmentioning
confidence: 50%
“…This may be related to the fact that most of our patients had severe TBI, so the reason may be that the associated hypertension and/or bradycardia commonly present in patients with severe TBI could alter SIPA values. It was reported that in cases of head trauma, SIPA elevation upon arrival was correlated with a longer stay in the hospital [28]. However, we could not perform serial measurements of SIPA due to the retrospective nature of our study.…”
Section: Discussionmentioning
confidence: 91%
“…They found that patients with severe blunt injuries initially presenting with a normal SIPA, but later developing a positive SIPA within 24 hours, had a higher mortality rate compared to those with consistently normal SIPA within the first 48 hours of admission [ 19 ]. Similarly, patients with moderate blunt injuries, initially presenting with a normal SIPA upon arrival, but subsequently developing a positive SIPA within 24 hours, were associated with an increased length of stay and the need for transfusion within the first 24 hours of arrival [ 38 ]. Moreover, Marenco et al [ 21 ] reviewed the Department of Defense Trauma Registry for pediatric patients with warzone trauma (age ≤ 17 years) and found that patients with a positive SIPA at both pre-hospital and arrival to initial care showed increased incidence of intensive care unit (ICU) admission, mechanical ventilation requirement, and mortality.…”
Section: Discussionmentioning
confidence: 99%